Vitamin D levels and tumor necrosis factor-α activity in newly diagnosed patients with type 2 diabetes mellitus: An exploratory study in North-East India - Dubey, Rahul; Anju Barhoi Teli; Nath, Uttam Kumar; Devi, Bharati; Medhi, Anuradha Hazarika; Dharma Rao Vanamali (Asian Journal of Medical Sciences, 2024)
Background: Diabetes poses a global threat, leading to hospitalizations and premature death if not managed properly. It involves tumor necrosis factor-α (TNF-α), an inflammatory cytokine, which binds to TNF-α receptor-1, triggering sphingomyelinase, and ceramide production. Vitamin D acts as an anti-inflammatory agent, reducing inflammatory cytokines and proinflammatory cell growth, and benefiting diabetes mellitus (DM). Aims and Objectives: The primary objective was to compare serum Vitamin D and TNF-α levels in diabetics and non-diabetics. The secondary objective was to explore Vitamin D and TNF-α correlation in newly diagnosed type 2 diabetes. Materials and Methods: A case–control study involved 92 subjects in each group. Data included demographics, clinical assessments, glycemic parameters, Vitamin D, and TNF-α. Statistical analysis used student’s t-test and Pearson correlation (P<0.05). Results: The cohort comprised 34 females (36.96%) and 58 males (63.04%). Cases had significantly higher glycemic levels: FBG (247.2±53.92 mg/dL vs. 91.45±16.64 mg/dL), postprandial plasma glucose (319.7±72.08 mg/dL vs. 111.3±21.76 mg/dL), and glycated hemoglobin (HbA1c) (10.39±2.41% vs. 5.43±0.48%). Mean serum Vitamin D in cases (22.63 ng/mL) was significantly lower than controls (58.15 ng/mL), and mean TNF-α in cases (5.01 pg/mL) was higher than controls (4.63 pg/mL, P<0.0001). HbA1c negatively correlated with serum Vitamin D (r=−0.7461) and positively with TNF-α (r=0.7831). Vitamin D correlated negatively with TNF-α (r=−0.6481). Conclusion: The study revealed lower serum Vitamin D and higher TNF-α levels in cases, with a significant inverse association. It also found an inverse link between Vitamin D and HbA1c and a strong positive correlation between HbA1c and TNF-α. Recognizing Vitamin D and TNF-α’s diagnostic significance promises innovative strategies for managing type 2 DM.